Krukenberg tumor arising from bilateral lobular carcinoma, in a pregnant lady: a rare case report - Santosh, T; Rao, Epari Sanjeeva; Rao, B R Mohan (Annals of Pathology and Laboratory Medicine, 2015)
Metastatic ovarian tumors are thought to account for approximately 10–30% of malignant ovarian tumors. Krukenberg tumor refers to a malignancy in the ovary that metastasized from a primary site, classically the gastrointestinal tract, although it can arise in other tissues such as the breast (approx. 04%). Krukenberg tumor during pregnancy arising from breast is even rarer (0.1 - 0.2%). The presence of adnexal masses during pregnancy ranges from 1:81 to 1:2,500 pregnancies, but only 3% of these masses are malignant. Management of such cases can present as diagnostic & treatment dilemma. We report a case of 25 year primiparous female with Krukenberg tumor of breast origin.